2022
DOI: 10.1002/tea.21767
|View full text |Cite
|
Sign up to set email alerts
|

Leading instructional improvement in elementary science: State science coordinators' sense‐making about the Next Generation Science Standards

Abstract: The Next Generation Science Standards (NGSS), a reform effort "for states, by states," advances ambitious ideals for elementary science teaching, but the fate of these ideals will depend in part on the engagement of

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 73 publications
0
6
0
Order By: Relevance
“…Even within a single district, Cherbow et al (2020) found that each school in their study "faced significant vertical incoherence concerning the goals for adoption of reform science standards" and that this incoherence contributed to differing interpretations of NGSS reforms among teachers and administrators (p. 466). Similarly, in studying the sensemaking of district science coordinators around the NGSS, Haverly et al (2022) found three distinct themes in their understanding of science reform which were impacted by local contextual factors like involvement in professional work groups and participating in professional networks. These studies demonstrate that study of stakeholder sensemaking at each level of implementation is critical to understanding how reforms are translated to the classroom.…”
Section: Ngss Implementation and Teachersmentioning
confidence: 99%
“…Even within a single district, Cherbow et al (2020) found that each school in their study "faced significant vertical incoherence concerning the goals for adoption of reform science standards" and that this incoherence contributed to differing interpretations of NGSS reforms among teachers and administrators (p. 466). Similarly, in studying the sensemaking of district science coordinators around the NGSS, Haverly et al (2022) found three distinct themes in their understanding of science reform which were impacted by local contextual factors like involvement in professional work groups and participating in professional networks. These studies demonstrate that study of stakeholder sensemaking at each level of implementation is critical to understanding how reforms are translated to the classroom.…”
Section: Ngss Implementation and Teachersmentioning
confidence: 99%
“…Recognizing SEA content-area coordinators' likely importance for standards implementation, a handful of scholars have investigated how state coordinators support standards implementation in either mathematics (Reys & Lappan, 2007), science (Haverly et al, 2022;Hopkins, 2016;Hopkins et al, 2018Hopkins et al, , 2019, or social studies (Swan et al, 2016). Haverly et al (2022) emphasize the important role of state coordinators in bridging national reform efforts with districts, anticipating that "political or historicized conflicts could arise" in this work, but interviewed state science coordinators primarily about their understandings of the Next Generation Science Standards rather than taking up those conflicts directly. Hopkins et al (2018) studied research brokering among a professional association for current and former state science coordinators, including how its members facilitated internal and external connections to research.…”
Section: The Role Of Sea Content-area Coordinatormentioning
confidence: 99%
“…13–17). While Haverly et al (2022) note the importance of local control as a contextual factor that state science coordinators brought up as shaping their job responsibilities, there have been few investigations into the tensions that state coordinators experience in their efforts to engage in the activities described above—supporting instruction within a particular content area across an entire state through a focus on standards, assessment, professional development, and curricular resources. One notable exception is Hopkins et al’s (2022) research-practice partnership with state coordinators for multilingual learners, in which SEA coordinators report similar challenges in navigating local control and state politics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the NGSS framework explicitly connects scientific and technological literacies to possibilities for civic engagement, contending that “knowledge of science and engineering is required to engage with the major public policy issues of today” (NASEM, 2021, p. 7). From an equity and social justice perspective, these developments are significant and have garnered recent research attention (e.g., Haverly et al, 2022; Klaver et al, 2022; Leung & Cheng, 2022).…”
Section: Introductionmentioning
confidence: 99%